Improving the use of lifting velocity to predict repetitions to failure: a systematic review - Miras-Moreno, S.; Pérez-Castilla, A.; Weakley, J.; Rojas-Ruiz, F. J.; García-Ramos, A. (International Journal of Sports Physiology and Performance, 2025)
Background: A recent advancement in velocity-based training involves estimating the maximum number of repetitions to failure (RTF) by analyzing the fastest velocity recorded within a set. A systematic review examining the fundamental characteristics of the RTF-velocity relationship is still lacking.